Viraemia and Ebola virus secretion in survivors of Ebola virus disease in Sierra Leone: a cross-sectional cohort study. Issue 9 (September 2016) - Green, Edward; Hunt, Luke; Ross, J C Gareth; Nissen, Nina Marie; Curran, Tanya; Badhan, Anjna; Sutherland, Katherine A; Richards, Jade; Lee, James S; Allen, Samuel H; Laird, Steven; Blackman, Mandy; et al.
Summary: Background: In survivors of Ebola virus disease, clinical sequelae including uveitis, arthralgia, and fatigue are common and necessitate systematic follow-up. However, the infection risk to health-care providers is poorly defined. Here we report Ebola virus RT-PCR data for body site and fluid samples from a large cohort of Ebola virus survivors at clinic follow-up. Methods: In this cross-sectional cohort study, consecutive survivors of Ebola virus disease attending Kerry Town survivor clinic (Freetown, Sierra Leone), who had been discharged from the Kerry Town Ebola treatment unit, were invited to participate. We collected and tested axillary, blood, conjunctival, forehead, mouth, rectal, semen, urine, and vaginal specimens for presence of Ebola virus using RT-PCR. We regarded samples to be positive for Ebola virus disease if the cycle threshold was 40 or lower. We collected demographic data from survivors of their age, sex, time since discharge from the treatment unit, and length of acute admission in the Ebola treatment unit using anonymised standard forms. Findings: Between April 2, and June 16, 2015, of 151 survivors of Ebola virus disease invited to participate, 112 (74%) provided consent. The median age of participants was 21·5 years (IQR 14–31·5) with 34 (30%) participants younger than 16 years. 50 (45%) of 112 participants were male. We tested a total of 555 specimens: 103 from the axilla, 93 from blood, 92 from conjunctiva, 54 from forehead, 105 from mouth, 17 from the rectum, one from semen, 69 from urine, and 21 from the vagina. The median time from Ebola treatment unit discharge to specimen collection was 142 days (IQR 127–159). 15 participants had a total of 74 swabs taken less than 100 days from discharge. The semen sample from one participant tested positive for Ebola virus at 114 days after discharge from the treatment unit; specimens taken from the axilla, blood, conjunctiva, forehead, mouth, rectum, and urine of the same participant tested negative. All specimens from the other 111 participants tested negative. Interpretation: Patients recovering from Ebola virus disease who do not meet the case definition for acute disease pose a low infection risk to health-care providers 6 weeks after clearance of viraemia. Personal protective equipment after this time might be limited to standard barrier precautions, unless contact with fluids from sanctuary sites is envisaged. Funding: Save the Children International, Public Health England.